Los Angeles Family and Neighborhood Survey (L.A.FANS), Wave 1, Restricted Data Version 1, 2000-2001 - Pebley, Anne R. ([Verlag nicht ermittelbar], 2019)
This study includes a restricted data file for Wave 1 of the L.A.FANS data. To compare L.A.FANS restricted data, version 1 with other restricted data versions, see the table on the series page for the L.A.FANS data here. Data in this study are designed for use with the public use data files for L.A.FANS, Wave 1 (study 1). This file adds only a few variables to the L.A.FANS, Wave 1 public use files. Specifically, it adds a "pseudo-tract ID" which is a number from 1 to 65, randomly assigned to each census tract (neighborhood) in the study. It is not possible to link pseudo-tract IDs in any way to real tract IDs or other neighborhood characteristics. However, pseudo-tract IDs permit users to conduct analyses which take into account the clustered sample design in which neighborhoods (tracts) were selected first and then individuals were sampled within neighborhoods. Pseudo-tract IDs do so because they identify which respondents live in the same neighborhood. It also includes certain variables, thought to be sensitive, which are not available in the public use data. These variables are identified in the L.A.FANS Wave 1 Users Guide and Codebook. Finally, some distance variables and individual characteristics which are treated in the public use data to make it harder to identify individuals are provided in an untreated form in the Version 1 restricted data file. Please note that L.A. FANS restricted data may only be accessed within the ICPSR Virtual Data Enclave (VDE) and must be merged with the L.A. FANS public data prior to beginning any analysis. A Users' Guide which explains the design and how to use the samples are available for Wave 1 at the RAND website. Additional information on the project, survey design, sample, and variables are available from: Sastry, Narayan, Bonnie Ghosh-Dastidar, John Adams, and Anne R. Pebley (2006). The Design of a Multilevel Survey of Children, Families, and Communities: The Los Angeles Family and Neighborhood Survey, Social Science Research, Volume 35, Number 4, Pages 1000-1024 The Users' Guides (Wave 1 and Wave 2) RAND Documentation Reports page